Design and development of SEPIC DC-DC boost converter for photovoltaic application - Ibrahim Alhamrouni; M. K. Rahmat; F. A. Ismail; Mohamed Salem; Awang Jusoh; T. Sutikno (Institute of Advanced Engineering and Science, 2019)
This study highlights a new construction of SEPIC DC-DC converter. The proposed converter aims for some features such as high voltage gain, continuous input current and reduce stress on the power switch. In addition, the circuit construction ensurs the simplicity in design along with signicant cost saving, since its components are readily available and smaller in size compared to the off-shelf components. This type of converter can adjust the DC voltage to maintain its output voltage to be constant. Typically, SEPIC operated in equipment that uses battery and also in wide range input voltage DC power supply. The converter is designed for renewable energy application where it is able to regulate the output voltage of the Photovoltaic (PV). The converter has been analysed based on different switching frequencies and duty cycle. Thus the outcome of the proposed converter can be achieved by using D=0.45 and fs=30 kHz. The proposed converter is supplied by 26V as an input voltage and produces 300V output and gives 94% of efficiency.